An investigation into practices, issues and improvement opportunities of logistical outsourcing : a study of integrated warehouse services : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Science in Logistics and Supply Chain Management at Massey University - Rachmayani, Novianti (Massey University, 2008)
A pressure to maintain company's profitability and at the same time a need for the company to increase service level and productivity, has forced the organisation to re-engineer its business systems into a more efficient and effective process. Outsourcing has introduced a new concept to re-engineering the company's business system by transferring the company's non-core business to the experts. Outsourcing can be a tool to achieve the competitive advantage. Even though, unsuccessful outsourcing implementation due to poor planning of outsourcing strategy might result in many problems for the company. The reality is outsourcing is expected to be further developed in the future. Thus, there is plenty of room for logistical outsourcing growth. Nonetheless, the barriers of logistical outsourcing growth, such as poor outsourcing planning strategy causes the lack of understanding of outsourcing and lack of proper logistical infrastructure. These barriers result in the need to review the issues applicable in the practices of logistical outsourcing. This research, therefore, investigates practices, issues and improvement opportunities of logistical outsourcing with regards to the practices of Integrated Warehouse Services. The use of multi-strategy research by combining the qualitative and quantitative research leads to the achievement of the research objective. This research found that reasons to outsource, the selection of outsourced activities and outsourcing provider selection process were the most important factors in outsourcing decision making process. The practices of IWS has been identified to gain success in improving customer service, reducing product cost, improve productivity, improving information sharing, reducing response time and improving space utilisation. The outcomes of this research illustrates that there is a tendency to perceive provider selection process and criteria and also the logistical outsourcing agreements and relationships as the logistical outsourcing issues to have the most concern in the practices of Integrated Warehouse Services. This research also found that the company needs to have improvements in the outsourcing agreements and relationships, employees training of outsourcing concept and the selection process of outsourcing provider.
Some Bahasa Indonesian Language
Keywords: Indonesia; Business logistics; Contracting out; Warehouses; Management; Case studies